La parole aux communautés : nous sommes là! La vitalité des communautés de langues officielles en situation minoritaire. Rapport du Comité permanent des langues officielles - Lauzon, Guy (Gouvernement du Canada, Chambre des communes 39e Législature, 1er session, 2007)

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Language barriers to healthcare for linguistic minorities: The case of second language-specific health communication anxiety - Zhao, Yue; Segalowitz, Norman; Voloshyn, A.nastasiya; Chamoux, Estelle; Ryder, Andrew G. (Health Communication, 2021)
In this study we examined health communication anxiety (HCA) associated with language-discordant situations – that is, where people have to use their second language (L2) to communicate with health providers who are using their first language (L1). We adapted existing HCA scales in order to (1) assess L2 HCA in such situations separately for physical and mental/emotional health contexts and (2) control for potential confounds, such as HCA not related to L2 use and L2 communication anxiety not related to health, allowing us to obtain L2-specific measures of HCA. We examined the relationship between L2-specific HCA and willingness to use health services in language-discordant situations. English-speaking linguistic minority participants (N = 314) living in Québec, a predominantly French-speaking area of Canada, were recruited for online testing. The results revealed that, separately for both physical and mental/emotional health contexts, there were significant and meaningful L2-specific relations between HCA and willingness to use L2 health services – i.e., over and above general anxiety and discomfort about using an L2, and over and above general health communication anxiety. The effect was stronger for mental/emotional health contexts. The results are discussed in terms of their implications for understanding barriers to health services for linguistic minorities.